Prevalence and incidence of probable perinatal depression among women enrolled in Option B+ antenatal HIV care in Malawi - Harrington, Bryna J. (J Affect Disord, 2018)
BACKGROUND: Perinatal depression is a common condition of pregnancy and the postpartum period. Depression negatively affects engagement in HIV care, but systematic screening for perinatal depression is not done in most sub-Saharan African countries. Estimating the burden and timing of perinatal depression can help inform medical programs with the current scale-up of HIV care for pregnant women. METHODS: Women (n=299) initiating antiretroviral therapy for HIV were recruited from a government antenatal clinic in Malawi in 2015-2016 into a cohort study. Probable perinatal depression was assessed at enrollment and at 6 weeks and 3, 6, and 12 months postpartum with the Edinburgh Postnatal Depression Scale (EPDS) and Patient Health Questionnaire-9 (PHQ-9). We estimated point prevalence and incidence of depression as well as concordance between EPDS and PHQ-9 scores. RESULTS: One in ten women screened positive for probable antenatal depression, whereas 1-6% screened positive postpartum. Sensitivity analyses to account for loss to follow-up suggested that postpartum depression prevalence could have ranged from 1-11%. At postpartum time points, 0-3% of participants screened positive for incident probable depression. EPDS and PHQ-9 scores were concordant for 96% of assessments during antenatal and postpartum visits. LIMITATIONS: Lack of diagnostic psychiatric evaluation precludes actual diagnosis of major depression, and social desirability bias may have contributed to low postpartum scores. CONCLUSIONS: Probable depression was more common during the antenatal period than postpartum among our participants. Given the association between depression and negative HIV outcomes, screening for depression during pregnancy should be integrated into antenatal HIV care.